Powerful multicultural essays for innovative educators and leaders : optimizing "hearty" conversations - Obiakor, Festus E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
"Powerful Multicultural Essays for innovative Educators and Leaders is written for this day, age, and time. We need to tear down our walls of hatred to optimize "hearty" conversations. In addition, we need to challenge ourselves and our institutions to do the right things. We must revisit our inner spiritual connectivity--- there are biblical allusions that could buttress our understanding about multiculturalism. For instance, human valuing is the engine behind the Parable of the Good Samaritan and the Parable of the Sower. Should our goal not be to sow good seeds that bloom to be beautiful flowers and even grow to be strong trees? Should our actions be divorced from supporting those who are different from us? Reading this book will help us to answer these questions. As often as possible, we must be action-oriented and practical as we arrive at our central hub and enhance our potential or existential collaboration, consultation, and cooperation at all levels of our human interactions. This is a book for students of life, which means all of us! We are all learners whether we are students, teachers, community leaders, university professors and leaders, researchers, scholars, politicians, to mention a few. We all need to read this book to optimize conversations, create open and healthy environments, and advance our nations and world. The days for hiding from discourses are over! We can no longer sweep our problems and actions under the rug! And, we cannot divorce ourselves from our own realities. Hopefully, this book will yield remarkable fruitful dividends with regard to human valuing"-- Provided by publisher.
Keywords: Multicultural education -- United States.; Education -- Social aspects.; Multiculturalism.; Education -- Multicultural Education.; Educational strategies and policy: inclusion.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books